2011
DOI: 10.1073/pnas.1014818108
|View full text |Cite
|
Sign up to set email alerts
|

Language processing in the occipital cortex of congenitally blind adults

Abstract: Humans are thought to have evolved brain regions in the left frontal and temporal cortex that are uniquely capable of language processing. However, congenitally blind individuals also activate the visual cortex in some verbal tasks. We provide evidence that this visual cortex activity in fact reflects language processing. We find that in congenitally blind individuals, the left visual cortex behaves similarly to classic language regions: (i) BOLD signal is higher during sentence comprehension than during lingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
401
7
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 366 publications
(446 citation statements)
references
References 58 publications
36
401
7
2
Order By: Relevance
“…In recent years, the occipital cortex, as well as adjacent ventral areas such as the fusiform gyrus (16,17), have been the main regions of interest in the study of cross-modal phenomena in blindness. Multiple studies have shown that the occipital cortex takes over multiple sensory abilities traditionally belonging to other unimodal cortices, such as auditory (18,19), tactile (20), or higher cognitive functions, including language processing (21). However, in light of our results, neuroplastic reorganization in blindness is centralized-in network and graph theory sense-beyond the visual cortex or its direct functional connections.…”
Section: Discussioncontrasting
confidence: 42%
“…In recent years, the occipital cortex, as well as adjacent ventral areas such as the fusiform gyrus (16,17), have been the main regions of interest in the study of cross-modal phenomena in blindness. Multiple studies have shown that the occipital cortex takes over multiple sensory abilities traditionally belonging to other unimodal cortices, such as auditory (18,19), tactile (20), or higher cognitive functions, including language processing (21). However, in light of our results, neuroplastic reorganization in blindness is centralized-in network and graph theory sense-beyond the visual cortex or its direct functional connections.…”
Section: Discussioncontrasting
confidence: 42%
“…Averaging across word positions, responses are highest for sentences, weaker for word-lists and Jabberwocky, and weakest for nonword-lists ( Fig. 2A and Table 2), a pattern similar to the one observed previously in fMRI (28,51). It is worth noting that unlike in fMRI, where the responses to word-lists and Jabberwocky are similar in magnitude (28), the ECoG response to word-lists is generally higher than the response to Jabberwocky ( Fig.…”
Section: Resultsmentioning
confidence: 47%
“…We have already discussed Broca's area and the ATL; other language-related areas that are typically activated by this contrast include the left posterior temporal lobe and the angular gyrus (Bedny et al, 2011;Pallier et al, 2011;Fedorenko et al, 2012c). The difference between our results and previous studies cannot be attributed solely to the differences between production and comprehension; several production studies have revealed effects in these areas (Menenti et al, 2011Segaert et al, 2012Segaert et al, , 2013.…”
Section: Whole-brain Contrasts Of Complexity and Structurecontrasting
confidence: 56%
“…The sentence > list contrast in comprehension occasionally activates Broca's area (Bedny et al, 2011;Fedorenko et al, 2011;Pallier et al, 2011), but these effects are much less consistent than for the ATL . This suggests that this activation reflects the contribution of working memory resources or cognitive control mechanisms needed to parse difficult input rather than fundamental syntactic operations (Novick et al, 2005;Rogalsky et al, 2008).…”
Section: Introductionmentioning
confidence: 89%